The Structure of Executive Dysfunction in Depression and Anxiety - Warren, Stacie L. (J Affect Disord, 2020)
BACKGROUND: Although research has demonstrated that depression and anxiety are associated with problematic executive function (EF), results are often inconsistent and underspecified. Delineating specific EF impairments in depression and anxiety has the potential to provide a mechanistic account of symptom presentation and course in these highly co-occurring disorders. The present study evaluated associations between components of EF and symptom dimensions of depression (depressed mood) and anxiety (anxious apprehension, anxious arousal) using factor analyses and structural equation modeling. METHODS: Undergraduates (N = 1,123) completed self-report measures of EF in everyday life and of psychopathology. Based on a three-factor model (Miyake et al., 2000), item-level exploratory (n = 561) and confirmatory (n = 562) factor analyses were conducted on inhibition, shifting, and working memory scales chosen from the EF measure. Structural equation modeling tested the relationship of EF factors to dimensions of psychopathology using the total sample. RESULTS: A three-factor model of EF best fit the data and was replicated via confirmatory factor analysis. Depressed mood and anxious arousal evidenced broad deficits across all EF domains, whereas anxious apprehension evidenced shifting disruptions. LIMITATIONS: Perceived EF may not index the same constructs as performance-based EF tests. Further, the present study was restricted to college students, warranting replication in other samples. CONCLUSIONS: Findings suggest that depressed mood and anxious arousal are characterized by a general disruption in the ability to maintain task goals, whereas anxious apprehension is characterized by cognitive inflexibility. EF impairments are likely contributory factors in the maintenance of affective disorders.